Analysis of Photography Service Pricing at Grabedito Studio in Palu City - Lahabu, Selfina; Sugianto, Sugianto; Usman, Ernawaty; Yuniar, Latifah Sukmawati (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the pricing process at Grabedito Studio in Palu and the factors influencing it. Using a qualitative case study approach, data were collected through interviews, observations, and documentation. COGS was calculated using the Full Costing method, while pricing followed the Cost Plus Pricing approach. Results show that the applied price exceeds COGS, indicating a Value-Based Pricing element, emphasizing skill and service quality. This suggests that photography pricing is shaped not only by costs but also by perceived value and professionalism, supporting fair, competitive, and sustainable pricing strategies.